Perancangan Video Promosi Objek Wisata Pantai Kelingking, Nusa Penida, Bali: Perancangan Video Promosi Objek Wisata Pantai Kelingking, Nusa Penida, Bali - I Made Rama Wahyudi; Ni Nyoman Sri Witari; Jajang Suryana (Warna Komunikasi, 2025)
Kelingking Beach is one of the most well-known tourist attractions in the Nusa Penida Island region of Bali. Known for its iconic view of cliffs shaped like a pinky finger, which simultaneously becomes the main attraction of this beach's beauty. Although it is already well-known among tourists, the uniqueness and popularity of Kelingking Beach still require ongoing promotion to prevent it from being overshadowed by other tourist destinations on this Island of the Gods. The purpose of designing this promotional video is to help promote the Kelingking Beach tourist attraction more intensively through dissemination on various social media platforms. The design of this promotional video uses a research method that applies data collection techniques such as direct observation at the location, interviews with sources active at Kelingking Beach, and gathering library data and documentation about this tourist attraction. The data obtained is used as a reference basis in the creation of the video design concept and its supporting media. The result of this design is a narrative promotional video about a trip to Kelingking Beach with a duration of 05:58 minutes for YouTube. The content is persuasive, not only conveying visual beauty but also applying principles of visual communication design, aiming to influence public interest through a series of unique experiences on the journey to Kelingking Beach. The other design outputs are seven promotional support media in the form of t-shirt illustration designs, stickers, pins, video thumbnails, instastories, websites, and short videos for Instagram and Facebook reels, YouTube shorts.